Identification of a mutation in the beta cardiac myosin heavy chain gene in a family with hypertrophic cardiomyopathy. Issue 2 (February 1993) - al-Mahdawi, S; Chamberlain, S; Cleland, J; Nihoyannopoulos, P; Gilligan, D; French, J; Choudhury, L; Williamson, R; Oakley, C
Abstract : OBJECTIVE–To investigate the molecular genetic basis of the cause of disease in a family with hypertrophic cardiomyopathy. BACKGROUND–Mutation within the beta cardiac myosin heavy chain gene has been shown to be the pathogenetic mechanism underlying the disease in several families, though clear evidence of heterogeneity has been reported. PATIENTS–A family with a history of hypertrophic cardiomyopathy. RESULTS AND CONCLUSION–This paper reports a mutation at aminoacid position 908 within exon 23 of the beta cardiac myosin heavy chain gene, resulting in a conversion of a leucine to valine. This base substitution was identified in an individual with a confirmed family history but with equivocal symptoms of the disease. Inheritance of the mutation by his symptom free juvenile offspring demonstrates the application of the technique to presymptomatic diagnosis.